TOWARD A TRANSFORMATION OF PRACTICES IN TEACHER EDUCATION - Lenoir, Yves (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
ABSTRACT. This article underscores the need for a profound transformation in the training processes of future teachers, and thereby in teaching practices. The text first presents various grounds for this transformation, citing social, economic-political, teleological, axiological, epistemological, and psychological factors. It then focuses on teacher development practices that need to change, highlighting the modifications to be brought to educational objectives, and in particular underscoring the essential need for a new approach in terms of relationships to knowledge and to students and other teacher educators. Finally, the article offers approaches for change in teacher education. In so doing, it argues for the establishment of appropriate conditions, the piloting of change, and for changes in the context of training and evaluation processes. POUR UNE TRANSFORMATION DES PRATIQUES DE FORMATION À L'ENSEIGNEMENT RÉSUMÉ. L’article met en évidence la nécessité de modifier en profondeur les processus de formation des futurs enseignants et, par là, leurs pratiques d’enseignement. Dans un premier temps, il avance différents motifs justifiant cette exigence en faisant appel à des facteurs sociaux, économico-politiques, téléologiques et axiologiques, épistémologiques et psychologiques. Dans un deuxième temps, l’article se penche sur les pratiques de formation qui doivent changer en soulignant les modifications apportées aux finalités éducatives, en relavent l’impératif d’une nouvelle approche du rapport au savoir et du rapport tant aux étudiants qu’aux autres formateurs. Enfin, dans un troisième temps, des modalités de changement sont proposées. Sont ainsi abordées la mise en place de conditions appropriées, le pilotage du changement et les transformations elles-mêmes dans les pratiques de formation et dans les processus d’évaluation.